Contributions of MyD88-dependent receptors and CD11c-positive cells to corneal epithelial barrier function against Pseudomonas aeruginosa. Issue 1 (December 2017) - Metruccio, Matteo; Tam, Connie; Evans, David; Xie, Anna; Stern, Michael; Fleiszig, Suzanne
Abstract Previously we reported that corneal epithelial barrier function againstPseudomonas aeruginosa was MyD88-dependent. Here, we explored contributions of MyD88-dependent receptors using vital mouse eyes and confocal imaging. Uninjured IL-1R (−/−) or TLR4 (−/−) corneas, but not TLR2 (−/−), TLR5 (−/−), TLR7 (−/−), or TLR9 (−/−), were more susceptible toP. aeruginosa adhesion than wild-type (3.8-fold, 3.6-fold respectively). Bacteria adherent to the corneas of IL-1R (−/−) or TLR5 (−/−) mice penetrated beyond the epithelial surface only if the cornea was superficially-injured. Bone marrow chimeras showed that bone marrow-derived cells contributed to IL-1R-dependent barrier function.In vivo, but notex vivo, stromal CD11c+ cells responded to bacterial challenge even when corneas were uninjured. These cells extended processes toward the epithelial surface, and co-localized with adherent bacteria in superficially-injured corneas. While CD11c+ cell depletion reduced IL-6, IL-1β, CXCL1, CXCL2 and CXCL10 transcriptional responses to bacteria, and increased susceptibility to bacterial adhesion (>3-fold), the epithelium remained resistant to bacterial penetration. IL-1R (−/−) corneas also showed down-regulation of IL-6 and CXCL1 genes with and without bacterial challenge. These data show complex roles for TLR4, TLR5, IL-1R and CD11c+ cells in constitutive epithelial barrier function againstP. aeruginosa, with deta ils dependent uponin vivo conditions.